Papuan frogs of the genus Cophixalus (Anura: Microhylidae): new synonyms, new species, and a dichotomous key - Kraus, Fred (Zootaxa, 2012)
Cophixalus represents the most diverse genus of microhylid frogs. Within this group I show that two recently describedspecies are in fact synonyms of species described in the 19th Century. Proper recognition of one of these has been hinderedby the poor state of the syntypes and confused information presented in earlier literature. The second species was simplynot diagnosed against other members of the genus. I also describe five new species: one of these is known only from asingle specimen from far western New Guinea, two occupy the Papuan Peninsula in the east of that island, and two arerestricted to Woodlark Island off the southeastern tip of New Guinea. One of these new species had earlier been mis-iden-tified as C. pipilans, requiring me to herein provide a corrected comparison of features that distinguishes C. desticans fromC. pipilans. These taxonomic changes bring the number of Cophixalus species to 61, of which 42 inhabit New Guinea andimmediately adjacent islands. But much of this region remains poorly surveyed, and, undoubtedly, many additional spe-cies remain to be described. I provide the first dichotomous key for the Papuan members of this genus, which should facilitate description of additional species.